Recommended core outcome instruments for health‐related quality of life, long‐term control and itch intensity in atopic eczema trials: results of the HOME VII consensus meeting. (8th February 2021) - Thomas, K.S.; Apfelbacher, C.A.; Chalmers, J.R.; Simpson, E.; Spuls, P.I.; Gerbens, L.A.A.; Williams, H.C.; Schmitt, J.; Gabes, M.; Howells, L.; Stuart, B.L.; Grinich, E.; et al.
Summary: Background: The Harmonising Outcome Measures for Eczema (HOME) initiative has established a core outcome set of domains for atopic eczema (AE) clinical trials. Previous consensus meetings have agreed on preferred instruments for clinician‐reported signs (Eczema Area and Severity Index, EASI) and patient‐reported symptoms (Patient‐Oriented Eczema Measure, POEM). This paper reports consensus decisions from the HOME VII meeting. Objectives: To complete the core outcome set for AE by agreeing on core outcome instruments for the domains of quality of life (QoL), long‐term control and itch intensity. Methods: A face‐to‐face consensus meeting was held in Tokyo, Japan (8–10 April 2019) including 75 participants (49 healthcare professionals/methodologists, 14 patients, 12 industry representatives) from 16 countries. Consensus decisions were made by presentations of evidence, followed by whole and small group discussions and anonymous voting using predefined consensus rules. Results: It was agreed by consensus that QoL should be measured using the Dermatology Life Quality Index (DLQI) for adults, the Children's Dermatology Life Quality Index (CDLQI) for children and the Infant's Dermatology Quality of Life Index (IDQoL) for infants. For long‐term control, the Recap of Atopic Eczema (RECAP) instrument or the Atopic Dermatitis Control Test (ADCT) should be used. Consensus was not reached over the frequency of data collection for long‐term control. The peak itch numerical rating scale (NRS)‐11 past 24 h was recommended as an additional instrument for the symptom domain in trials of older children and adults. Agreement was reached that all core outcome instruments should be captured at baseline and at the time of primary outcome assessment as a minimum. Conclusions: For now, the core outcome set for clinical trials in AE is complete. The specified domains and instruments should be used in all new clinical trials and systematic reviews of eczema treatments. Abstract : What is already known about this topic? Core outcomes sets improve the design and reporting of clinical trials, reduce selective outcome reporting bias and facilitate meta‐analysis of results in systematic reviews. The HOME core outcome set for eczema recommends the inclusion of four core domains in all atopic eczema trials: clinician‐reported signs, patient‐reported symptoms, health‐related quality of life (HrQoL) and long‐term control. Clinician‐reported signs should be captured using the Eczema Area and Severity Index (EASI) and patient‐reported symptoms using the Patient‐Oriented Eczema Measure (POEM). What does this study add? The HOME core outcome set is now complete and recommended core outcome instruments have been agreed on for all four domains. Core outcome instruments for HrQoL: Dermatology Life Quality Index (DLQI) for adults, Children's Dermatology Life Quality Index (CDLQI) for children and Infant's Dermatology Quality of Life Index (IDQoL) for infants. Core outcome instruments for long‐term control: either the Recap of Atopic Eczema (RECAP) or the Atopic Dermatitis Control Test (ADCT). In addition, itch intensity should be measured using the peak NRS‐11 past 24 h for trials including older children and adults. What are the clinical implications of this work? If all future trials of eczema treatments include the HOME core outcome instruments, then trial results will be more readily incorporated into meta‐analyses in systematic reviews and clinical care will be informed by the best available evidence. Linked Comment:  D.F. Murrell and C.F. Paul. Br J Dermatol 2021; 185 :13–14 .